Critical Thinking Skills of Fourth Grade in Light Properties Materials through the Radec Model - Karlina, Dina; Sopandi, Wahyu; Sujana, Atep (International Conference on Elementary Education, 2020)
The purpose of this study is to determine the effect of the Read, Answer, Disscuss, Explain and Create (RADEC) models on the critical thinking skills of elementary school students. The research method used in this study is a quasi-experimental method with one group pretest postest design. The study was conducted in fourth grade students of state primary schools in Sumedang Regency. The sample used in the study amounted to 27 students. Consisting of 12 male students and 15 female students. The instruments used were tests of critical thinking questions, observation sheets and questionnaires. Critical thinking skills tests were carried out with two stages of pretest and posttest. Data processing techniques using SPSS for window version 23. From this study, the average score of students' critical thinking skills pretest was 68.33 while the average posttest score was 82.22. The Mann-Whitney test results obtained the value of sig = 0,000. This shows that there are significant differences in the average value of pretest and posttest. Next, the N-gain value of 0.4 is obtained. So it is interpreted that there is a significant difference in the critical thinking skills of fourth grade students on the material properties of light before and after treatment using the RADEC learning model. Therefore, it can be concluded that students' critical thinking skills have increased in the medium category through the RADEC model